Understanding of Mathematical Concepts and Students’ Self-Regulated Learning in RME Learning Assisted by PANDU - Citra Utami; Rien Anitra; Usinah Robert Moseki (STKIP Singkawang, 2020)
The understanding of mathematical concepts has an important role in one of the knowledge and activity skills in mathematics learning according to NCTM. On the other hand, self-regulated learning is one aspect that also determines the success of students' mathematics learning. Facts in the field, the understanding of concepts, and self-regulated learning students' are still low. Based on this, the need for contextual learning and the existence of teaching aids in learning mathematics. The purpose of this study is to find out the increase in understanding of the concept, the effect of self-regulated learning toward the understanding of concepts, and describe the understanding of the concept. This research is a mixed-method with a combination model used in Sequential Explanatory Design. The subjects were fourth-grade elementary school students in the city of Singkawang. In the qualitative part, taking the subject is to randomly select 1 student from the criteria of understanding the concepts that arise. Data collection instruments used were tests and questionnaires. The data analysis technique used is the scoring, N-Gain test, simple regression test, and quantitative descriptive. The results of this study showed: (1) there is an increase in understanding of concepts in RME learning assisted by PANDU; (2) there is a significant influence between self-regulated learning and the understanding of concepts in RME learning assisted by PANDU, and (3) the understanding of concepts in learning RME assisted by PANDU has an average of 79.63.